The effect of multicultural family structures on the language attitudes of children and adolescents - Lee, Hugo Yu-Hsiu (Penerbit Universiti Kebangsaan Malaysia, 2018)
Attitudes toward languages of bi- and multilingual children and adolescents have not yet become a focus of research. Despite rapid growth in the number of bi- and multilingual children and adolescents across the globe, surprisingly few studies have been devoted to this significant phenomenon. Bi- and multilingualism is a major consequence of immigration and cross-cultural marriages. Regardless of whether cross-cultural marriage is involved, the immigration of families has considerable linguistic consequences on children and adolescents. This paper draws on five case studies in examining the complex factors determining the attitudinal patterns evinced by bi- and multilingual children and adolescents from immigrant families in Thailand. Five households agreed to participate in this research endeavor and data were also collected from surveys, interviews, observations and field notes acquired through the employment of ethnographic investigative methods. The data collected were analyzed through constant comparative method and content analysis. Findings showed consistent patterns for those bi- and multilingual children and adolescents whose Thaispeaking mother was linguistically dominant in a family with an immigrant father speaking a minority language. The results showed that these children were more likely to perceive Thai as more highly regarded language. By contrast, it was also found that Thai was not as highly regarded by the children of parents if both were minority-language speaking immigrants. It was concluded that the family structure of immigrant families is associated with the language attitudes of their children. By the same token, the type of marriage of immigrant families has long-reaching effects on the development of children and adolescents’ language attitudes. Moreover, data showed that a non-migrant mother’s dominant language played a more influential role in contrast to the minimal role-played by the migrant father’s minority language in the development of children and adolescents’ language attitudes.